2010
DOI: 10.1073/pnas.1010390107
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of 5-hydroxyisourate hydrolase causes hepatomegaly and hepatocellular carcinoma in mice

Abstract: With the notable exception of humans, uric acid is degraded to (S)-allantoin in a biochemical pathway catalyzed by urate oxidase, 5-hydroxyisourate (HIU) hydrolase, and 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoline decarboxylase in most vertebrate species. A point mutation in the gene encoding mouse HIU hydrolase, Urah, that perturbed uric acid metabolism within the liver was discovered during a mutagenesis screen in mice. The predicted substitution of cysteine for tyrosine in a conserved helical region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Even their dismutation to dehydrourate may be harmful because this species hydrolyzes to 5-hydroxyisourate (Scheme 2). This metabolite, which was produced by MPO, has recently been shown to be associated with development of liver tumors in mice (59). Adverse reactions of urate radicals will be kept in check only when ascorbate is available at sufficient concentrations to reduce them back to urate (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Even their dismutation to dehydrourate may be harmful because this species hydrolyzes to 5-hydroxyisourate (Scheme 2). This metabolite, which was produced by MPO, has recently been shown to be associated with development of liver tumors in mice (59). Adverse reactions of urate radicals will be kept in check only when ascorbate is available at sufficient concentrations to reduce them back to urate (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…The first level concerns the evolutionary change of the HIUase peroxisomal targeting signal (PTS) into a signal peptide in TTR. In this respect, it should be pointed out that HIUase in mouse and, presumably, in other vertebrates is confined to hepatocytes, 7 where the urate degradation pathway takes place. Given the same intron/ exon structures of the genes encoding HIUase and TTR, the first coding exon encodes a signal peptide in TTR and a type 2 PTS in HIUase.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, an inactivating mutation in HIUase leads to hepatomegaly and hepatocellular carcinoma. 7 HIUase is a tetramer formed by the assembly of four identical subunits and characterized by a 222 symmetry. Each monomer is composed of eight antiparallel β-strands, arranged in a topology similar to that of the Greek key β-barrel, and a short α-helix.…”
mentioning
confidence: 99%
“…Dehydrourate and 5-hydroxyisourate are electrophilic species that are potentially toxic and are likely to affect host defense as well as the inflammatory response to bacteria. The absence of 5-hydroxyisourate hydrolase in knock-out mice predisposes them to liver cancer (61), which demonstrates that these electrophiles are indeed toxic. In the presence of superoxide, we have shown that LPO catalyzes the production of another electrophile, urate hydroperoxide.…”
Section: Discussionmentioning
confidence: 99%